The amygdala: securing pleasure and avoiding pain - Fernando, Anushka B.; Murray, Jennifer E.; Milton, Amy L. (Frontiers in Behavioral Neuroscience, 2013)
The amygdala has traditionally been associated with fear, mediating the impact of negative emotions on memory. However, this view does not fully encapsulate the function of the amygdala, nor the impact that processing in this structure has on the motivational limbic corticostriatal circuitry of which it is an important structure. Here we discuss the interactions between different amygdala nuclei with cortical and striatal regions involved in motivation; interconnections and parallel circuitries that have become increasingly understood in recent years. We review the evidence that the amygdala stores memories that allow initially motivationally neutral stimuli to become associated through pavlovian conditioning with motivationally relevant outcomes which, importantly, can be either appetitive (e.g. food) or aversive (e.g. electric shock). We also consider how different psychological processes supported by the amygdala such as conditioned reinforcement and punishment, conditioned motivation and suppression, and conditioned approach and avoidance behavior, are not only psychologically but also neurobiologically dissociable, being mediated by distinct yet overlapping neural circuits within the limbic corticostriatal circuitry. Clearly the role of the amygdala goes beyond encoding aversive stimuli to also encode the appetitive, requiring an appreciation of the amygdala’s mediation of both appetitive and fearful behavior through diverse psychological processes.